Resin composition and its products

By using resin compositions with specific structures, the problem that existing materials cannot meet the requirements of high heat resistance and low thermal expansion is solved, and higher multilayer board heat resistance and lower thermal expansion are achieved, suitable for copper clad plates and printed circuit boards.

CN119751777APending Publication Date: 2025-04-04ELITE ELECTRONIC MATERIAL (KUNSHAN) CO LTD

Patent Information

Application Number
CN202311264680.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing copper clad plate and its resin composition cannot meet the requirements of higher multilayer plate heat resistance, lower Z-axis thermal expansion rate, reflow solder warpage, dielectric loss aging rate, dielectric constant temperature coefficient and dielectric loss temperature coefficient.

Method used

A resin composition is provided, comprising 100 parts by weight of a copolymer composed of structural units formed of a specific monomer, and the content of structural units formed of monomers represented by formula (2) accounts for 55% to 90% by weight of the copolymer; and 10 to 60 parts by weight of the compound represented by formula (3).

Benefits of technology

The resin composition can significantly reduce the Z-axis thermal expansion rate, reflow solder warpage, dielectric loss aging rate, dielectric constant temperature coefficient and dielectric loss temperature coefficient, improve the heat resistance of multi-layer boards, and is suitable for semi-cured sheets, resin films, laminated boards and printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751777A_ABST
    Figure CN119751777A_ABST
Patent Text Reader

Abstract

The present invention discloses a resin composition, which comprises (A) 100 parts by weight of a copolymer, wherein the copolymer has a structural unit formed by a monomer shown in formula (1) and a structural unit formed by a monomer shown in formula (2), and the content of the structural unit formed by the monomer shown in formula (2) accounts for 55wt% to 90wt% of the copolymer; and (B) 10 parts by weight to 60 parts by weight of a compound shown in formula (3). In addition, the present invention also discloses an article made of the above-mentioned resin composition. The above-mentioned article includes a prepreg, a resin film, a laminate or a printed circuit board, and can be improved in one or more aspects such as reflow soldering warpage, Z-axis thermal expansion coefficient, heat resistance of a multilayer board, dielectric loss aging rate, dielectric constant temperature coefficient and dielectric loss temperature coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention mainly relates to a resin composition and products made from the same, and in particular to a resin composition applicable to prepregs, resin films, laminates (such as copper foil substrates) and printed circuit boards and products made from the same. Background Art

[0002] As a basic electronic component, printed circuit boards (PCBs) are used in many fields including mobile phones, computers, communication base stations, data centers, automobiles, industrial control, aerospace, etc. Their technical level and reliability have a direct impact on the performance and stability of electronic equipment. Copper clad laminate (CCL, or copper foil laminate) is the substrate material of PCB. It mainly plays the role of interconnection, insulation and support for PCB. It has a great influence on the transmission speed, energy loss, characteristic impedance and other aspects of the signal in the circuit. The performance, quality, processability, reliability, stability and other characteristics of PCB depend to a large extent on the performance and quality of copper clad laminate.

[0003] The problems of process capability, signal integrity, heat dissipation and stress currently faced by advanced PCB packaging technology have put forward higher requirements for the performance of copper clad laminates: higher heat resistance of multilayer boards, lower Z-axis thermal expansion rate, reflow soldering warpage, dielectric loss aging rate, dielectric constant temperature coefficient and dielectric loss temperature coefficient. However, existing copper clad laminates and their resin compositions still mainly focus on the general conventional properties of copper clad laminates.

[0004] Therefore, the art urgently needs to develop resin compositions and copper-clad laminates having lower Z-axis thermal expansion coefficient, reflow soldering warpage, dielectric loss aging rate, dielectric constant temperature coefficient and dielectric loss temperature coefficient, while also having higher heat resistance of multilayer boards. Summary of the invention

[0005] In view of the above-mentioned technical problems existing in the prior art, especially the problem that existing materials cannot meet one or more of the above-mentioned performance requirements, the main purpose of the present invention is to provide a resin composition that can overcome at least one of the above-mentioned technical problems, and a product made of the resin composition.

[0006] The first aspect of the present invention provides a resin composition comprising the following components:

[0007] (A) 100 parts by weight of a copolymer, the copolymer having a structural unit formed from a monomer represented by formula (1) and a structural unit formed from a monomer represented by formula (2), wherein the content of the structural unit formed from the monomer represented by formula (2) accounts for 55 wt % to 90 wt % of the copolymer; and

[0008] (B) 10 to 60 parts by weight of a compound represented by formula (3),

[0009]

[0010] Wherein, in the formula (1), R1 to R5 are each independently selected from a hydrogen atom, a C1 to C3 alkyl group, a C2 to C3 alkenyl group, a phenyl group, a C1 to C3 alkyl-substituted phenyl group, a C2 to C3 alkenyl-substituted phenyl group, and a C2 to C3 alkenylphenyl C1 to C3 alkylene group;

[0011] In the formula (2), R6 to R9 are each independently selected from a hydrogen atom, a C1 to C3 alkyl group and a C2 to C3 alkenyl group, and at least one of R6 to R9 is a C2 to C3 alkenyl group;

[0012] In the formula (3), n is an integer of 3 to 6, and X and Y each independently represent an o-vinylphenoxy group, a m-vinylphenoxy group or a p-vinylphenoxy group.

[0013] For example, in one embodiment, the copolymer is composed of structural units formed by monomers represented by formula (1) and structural units formed by monomers represented by formula (2), and the content of the structural units formed by the monomers represented by formula (2) accounts for 55wt% to 90wt% of the copolymer.

[0014] For example, in one embodiment, the monomer represented by formula (1) includes any one of the monomer represented by formula (1-1), the monomer represented by formula (1-2), the monomer represented by formula (1-3), and the monomer represented by formula (1-4), or a combination thereof, and the monomer represented by formula (2) includes the monomer represented by formula (2-1).

[0015]

[0016]

[0017] For example, in one embodiment, the copolymer includes any one of a block copolymer and a random copolymer or a combination thereof. Preferably, the copolymer is a block copolymer.

[0018] For example, in one embodiment, the copolymer includes any one or a combination of the copolymers represented by the following formulas (4) to (19):

[0019]

[0020]

[0021] In the above formulas (4) to (19), m, n, x, y, and z are each independently a positive integer and satisfy the following relationship: 2≦m≦44, 12≦n≦70, 2≦x+z≦44, 12≦y≦70.

[0022] For example, in one embodiment, the compound represented by formula (3) includes any one or a combination of the compound represented by formula (3-1) to the compound represented by formula (3-14),

[0023]

[0024]

[0025]

[0026] For example, in one embodiment, the resin composition further comprises 1 to 30 parts by weight of a cross-linking agent containing unsaturated carbon-carbon double bonds, wherein the cross-linking agent containing unsaturated carbon-carbon double bonds is any one of bis(vinylphenyl)ethane, divinylbenzene, divinylnaphthalene, divinylbiphenyl, triallyl isocyanurate, triallyl cyanurate, vinylbenzocyclobutene, di(vinylbenzyl)ether, trivinylcyclohexane, diallyl bisphenol A, difunctional or higher acrylate, butadiene, decadiene, octadiene, or a combination thereof.

[0027] For example, in one embodiment, the resin composition further comprises any one of a polyolefin different from the copolymer, a polyphenylene ether resin containing unsaturated carbon-carbon double bonds, a benzoxazine resin, an epoxy resin, a polyester resin, a phenolic resin, an amine curing agent, a polyamide, a polyimide, styrene maleic anhydride, a maleimide resin, a cyanate ester, and a maleimide triazine resin, or a combination thereof.

[0028] For example, in one embodiment, the resin composition further comprises an inorganic filler, a flame retardant different from the compound represented by formula (3), a hardening accelerator, an inhibitor, a solvent, a silane coupling agent, a colorant, a toughening agent, or any one or a combination thereof.

[0029] Another aspect of the present invention provides a product made of the above resin composition, wherein the product includes a prepreg, a resin film, a laminate or a printed circuit board.

[0030] For example, in one embodiment, the article has one or more of the following characteristics:

[0031] The reflow soldering warpage measured by the Full-field Signed Warpage test method is less than or equal to 10μm;

[0032] The Z-axis thermal expansion rate measured according to IPC-TM-650 2.4.24.5 is less than or equal to 1.0%;

[0033] After standing at a constant temperature of 125°C for 240 hours, the dielectric loss aging rate calculated by the dielectric loss measured at a frequency of 10 GHz according to the method of JIS C2565 is less than or equal to 60%;

[0034] The dielectric constant temperature coefficient measured according to IPC-TM-650 2.5.5.13 is less than or equal to 70ppm / ℃;

[0035] The dielectric loss temperature coefficient measured according to IPC-TM-650 2.5.5.13 is less than or equal to 4000ppm / ℃. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text have the common meanings understood by those skilled in the art for the present invention. In case of conflict, the definitions in this specification shall prevail.

[0037] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0038] The use of "one", "a", "an" or similar expressions to describe the components and technical features of the present invention is merely for the convenience of expression and to provide a general meaning to the scope of the present invention. Therefore, such description should be understood to include one or at least one, and the singular also includes the plural, unless it is obvious that it refers to another meaning.

[0039] As used herein, the terms "comprises," "includes," "has," "contains," or any other similar terms are open-ended transitional phrases, which are intended to cover non-exclusive inclusions. For example, a composition or article comprising a plurality of elements encompasses any one or any one of the listed elements, and is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless expressly stated to the contrary, the term "or" refers to an inclusive "or" rather than an exclusive "or." For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, in this article, the terms "comprising", "including", "having", and "containing" should be interpreted as being specifically disclosed and simultaneously covering closed conjunctions such as "consisting of", "consisting of", "the remainder of", and conjunctions such as "consisting essentially of", "mainly consisting of", "mainly consisting of", "basically containing", "essentially consisting of", "essentially consisting of", and "essentially containing".

[0040] As used herein, “or a combination thereof” means “or any combination thereof”, covering any combination of more than two of the listed elements; “any one”, “any one”, “any one” means “any one”, “any one”, “any one”. For example, “a composition or its product includes A, B, C or a combination thereof”, when interpreted, covers the following situations: A is true (or exists) and B and C are false (or do not exist), B is true (or exists) and A and C are false (or do not exist), C is true (or exists) and A and B are false (or do not exist), A and B are true (or exist) and C is false (or do not exist), A and C are true (or exist) and B is false (or do not exist), B and C are true (or exist) and A is false (or do not exist), A, B and C are all true (or exist), and other elements not explicitly listed but that are typically inherent to the composition or its product.

[0041] In this article, the terms "and", "with", "and", "as well as" or other similar terms are used to connect parallel sentence components, and there is no distinction between the previous and subsequent components. The meaning of the parallel sentence components does not change after the positions of the parallel sentence components are exchanged in grammatical sense.

[0042] In this article, all features or conditions such as numerical values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions), especially integer values. For example, the range description of "1.0 to 8.0", "between 1.0 and 8.0" or "between 1.0 to 8.0" should be deemed to have specifically disclosed all sub-ranges such as 1.0 to 8.0, 1.0 to 7.0, 2.0 to 8.0, 2.0 to 6.0, 3.0 to 6.0, 4.0 to 8.0, 3.0 to 8.0, etc., and should be deemed to cover endpoint values, especially sub-ranges defined by integer values, and should be deemed to have specifically disclosed individual values ​​such as 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, etc. Unless otherwise indicated, the above explanation method applies to all contents of the entire text of the present invention, regardless of whether the scope is broad or not.

[0043] If the quantity, concentration or other numerical value or parameter is expressed as a range, a preferred range (or a better range) or a series of upper and lower limits, it should be understood that all ranges consisting of any pair of the upper limit or preferred value (or a better value) of the range and the lower limit or preferred value (or a better value) of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.

[0044] In this document, numerical values ​​should be understood to have the accuracy of the number of significant digits of the numerical value, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range of 39.50 to 40.49.

[0045] In this article, for the use of Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that all subgroups or any individual elements in the Markush group or option list can also be used to describe the present invention. For example, if X is described as "selected from the group consisting of X1, X2 and X3", it also means that the claim that X is X1 and the claim that X is X1 and / or X2 and / or X3 have been fully described. Furthermore, for the use of Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that any combination of subgroups or individual members of all elements in the Markush group or option list can also be used to describe the present invention. Accordingly, for example, if X is described as "selected from the group consisting of X1, X2 and X3", and Y is described as "selected from the group consisting of Y1, Y2 and Y3", it means that the claim that X is X1 and / or X2 and / or X3 and Y is Y1 and / or Y2 and / or Y3 has been fully described.

[0046] Unless otherwise specified, in the present invention, a compound refers to a chemical substance formed by two or more elements connected by chemical bonds, including small molecule compounds and polymer compounds, but not limited thereto. The compound herein is not limited to a single chemical substance when interpreted, but can also be interpreted as the same type of chemical substances with the same composition or the same properties.

[0047] If not otherwise specified, in the present invention, polymer refers to the product formed by the polymerization reaction of monomers, often including many polymer aggregates, each polymer is composed of many simple structural units repeatedly connected by covalent bonds, and the monomer is a compound of the synthetic polymer. Polymers can include homopolymers, copolymers, prepolymers, etc., and are not limited to this. Homopolymers refer to polymers polymerized from one monomer. Copolymers refer to polymers polymerized from two or more monomers. Copolymers include random copolymers (structures such as -AABABBBAAABBA-), alternating copolymers (structures such as -ABABABAB-), graft copolymers (structures such as -AA(A-BBBB)AA(A-BBBB)AAA-) and block copolymers (structures such as -AAAAA-BBBBBB-AAAAA-), etc. For example, the styrene-butadiene copolymer in the present invention can include styrene-butadiene random copolymers, styrene-butadiene alternating copolymers, styrene-butadiene graft copolymers or styrene-butadiene block copolymers when interpreted. Prepolymer refers to a polymer with a lower molecular weight between the monomer and the final polymer, and the prepolymer contains reactive functional groups that can further undergo polymerization to obtain a fully cross-linked or hardened product with a higher molecular weight. Polymers of course include oligomers, but are not limited to them. Oligomers, also known as low polymers, are polymers composed of 2 to 20 repeating units, usually 2 to 5 repeating units.

[0048] For those skilled in the art, a resin composition containing three compounds A, B and C and an additive (comprising four components in total), and a resin composition containing a prepolymer formed by three compounds A, B and C and an additive (comprising two components in total) are different resin compositions, and the two are completely different in many aspects such as the preparation method, the physical and chemical properties of the compounds themselves, and the properties of their products. For example, the former is to mix A, B, C and additives to form a resin composition, while the latter is to first prepolymerize the mixture including A, B and C under appropriate conditions to form a prepolymer, and then mix the prepolymer with the additive to obtain a resin composition. For example, for those skilled in the art, the above two resin compositions have completely different compositions, and because the function of the prepolymer formed by the three compounds A, B and C in the resin composition is completely different from the function of A, B and C individually or together in the resin composition, the two resin compositions should be regarded as completely different chemical substances with completely different chemical positions. For example, for those skilled in the art, because the above two resin compositions are completely different chemical substances, their products will not have the same properties. For example, a resin composition including a prepolymer formed by three compounds A, B and C and a crosslinking agent, since A, B and C have partially reacted or converted during the prepolymerization reaction to form the prepolymer, when the resin composition is subsequently heated at a high temperature to form a semi-cured state, a partial crosslinking reaction occurs between the prepolymer and the crosslinking agent, rather than A, B and C each undergoing a partial crosslinking reaction with the crosslinking agent. Therefore, the products formed by the two resin compositions will also be completely different and have completely different properties.

[0049] If not otherwise specified, the "resin" in the present invention is a customary name for a synthetic polymer, which may include monomers, polymers thereof, combinations of monomers, combinations of polymers thereof, or combinations of monomers and polymers thereof, etc., and is not limited thereto.

[0050] If not otherwise specified, in the present invention, modified products include products after modification of reactive functional groups of each resin, products after prepolymerization of each resin with other resins, products after crosslinking of each resin with other resins, products after copolymerization of each resin with other resins, and the like.

[0051] If not otherwise specified, the unsaturated bond described in the present invention refers to a reactive unsaturated bond, such as but not limited to an unsaturated double bond that can undergo a cross-linking reaction with other functional groups, such as but not limited to an unsaturated carbon-carbon double bond that can undergo a cross-linking reaction with other functional groups.

[0052] The unsaturated carbon-carbon double bond described in the present invention preferably includes but is not limited to vinyl, vinylbenzyl, (meth)acryloyl, allyl or a combination thereof. Vinyl should be interpreted to include vinyl and vinylidene, and (meth)acryloyl should be interpreted to include acryloyl and methacryloyl.

[0053] Unless otherwise specified, the alkyl, alkenyl, and monomers described in the present invention include their various isomers when interpreted. For example, propyl should be interpreted as including n-propyl and isopropyl.

[0054] Unless otherwise specified, in the present invention, parts by weight represent relative parts by weight in the composition, which may be any weight unit, such as but not limited to kilograms, kilograms, grams, pounds, etc. For example, 100 parts by weight of a copolymer may represent 100 kilograms of the copolymer or 100 pounds of the copolymer.

[0055] Unless otherwise specified, in the present invention, wt% represents weight (or mass) percentage.

[0056] It should be understood that the features disclosed in the various embodiments herein may be arbitrarily combined to form the technical solution of the present invention, as long as there is no contradiction in the combination of these features.

[0057] The present invention will be described below with specific embodiments and examples. It should be understood that these specific embodiments and examples are merely exemplary and are not intended to limit the scope of the present invention and its use. The methods, reagents and conditions used in the examples are, unless otherwise stated, methods, reagents and conditions conventional in the art.

[0058] As mentioned above, the present invention mainly discloses a resin composition, comprising the following components:

[0059] (A) 100 parts by weight of a copolymer, the copolymer having a structural unit formed from a monomer represented by formula (1) and a structural unit formed from a monomer represented by formula (2), wherein the content of the structural unit formed from the monomer represented by formula (2) accounts for 55 wt % to 90 wt % of the copolymer; and

[0060] (B) 10 to 60 parts by weight of a compound represented by formula (3),

[0061]

[0062] wherein, in formula (1), R1 to R5 are each independently selected from a hydrogen atom, a C1 to C3 alkyl group (e.g., methyl, ethyl or propyl group), a C2 to C3 alkenyl group (e.g., vinyl or allyl group), a phenyl group, a C1 to C3 alkyl-substituted phenyl group (e.g., ethylphenyl group), a C2 to C3 alkenyl-substituted phenyl group (e.g., vinylphenyl group) and a C2 to C3 alkenylphenyl C1 to C3 alkylene group (e.g., vinylphenyl ethylene group);

[0063] In formula (2), R6 to R9 are each independently selected from a hydrogen atom, a C1 to C3 alkyl group (e.g., a methyl group, an ethyl group, or a propyl group) and a C2 to C3 alkenyl group (e.g., a vinyl group or an allyl group), and at least one of R6 to R9 is a C2 to C3 alkenyl group (e.g., a vinyl group or an allyl group);

[0064] In formula (3), n is an integer from 3 to 6 (e.g., 3, 4, 5 or 6), and X and Y each independently represent an o-vinylphenoxy group, a m-vinylphenoxy group or a p-vinylphenoxy group. The structures of the o-vinylphenoxy group, the m-vinylphenoxy group and the p-vinylphenoxy group are as follows (wherein * represents the position of bonding to the phosphorus atom):

[0065] o-Vinylphenoxy:

[0066] m-Vinylphenoxy:

[0067] p-Vinylphenoxy:

[0068] For example, in one embodiment, the copolymer is composed of structural units formed by monomers represented by formula (1) and structural units formed by monomers represented by formula (2), and the content of the structural units formed by the monomers represented by formula (2) accounts for 55wt% to 90wt% of the copolymer.

[0069] For example, in one embodiment, the monomer represented by formula (1) includes any one of the monomer represented by formula (1-1), the monomer represented by formula (1-2), the monomer represented by formula (1-3), and the monomer represented by formula (1-4), or a combination thereof, and the monomer represented by formula (2) includes the monomer represented by formula (2-1).

[0070]

[0071] For example, in one embodiment, the copolymer is preferably a random copolymer or a block copolymer, more preferably a block copolymer.

[0072] For example, in one embodiment, the copolymer includes any one or a combination of the copolymers represented by the following formulas (4) to (19):

[0073]

[0074]

[0075] In formula (4) to formula (19), m, n, x, y, and z are each independently a positive integer and satisfy the following relationship: 2≦m≦44, 12≦n≦70, 2≦x+z≦44, 12≦y≦70. For example, but not limited to, m=2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, or 44; n=12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69 or 70; x+z=2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, or 44; y=12, 13, 14, 15, 16, 17, 18, 19 , 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69 or 70. And in formula (4) to formula (19), the content of the structural unit formed by the monomer represented by formula (2) is 55wt% to 90wt%.

[0076] The copolymers represented by the above formulae (4) to (19) are merely illustrative, and the form of the copolymers is not limited thereto. The copolymers represented by formulae (4) to (11) can be interpreted as block copolymers, and the copolymers represented by formulae (12) to (19) can be interpreted as random copolymers.

[0077] The copolymer having the structural unit formed by the monomer represented by formula (1) and the structural unit formed by the monomer represented by formula (2) of the present invention can be prepared by various methods known to those skilled in the art. For example, the copolymer can be prepared by the following method:

[0078] 1. A copolymer having a structural unit formed from a monomer represented by formula (1) and a structural unit formed from a monomer represented by formula (2) is a block copolymer.

[0079] At 0°C to 40°C and in an inert atmosphere, a solvent and an anionic initiator are added to a reaction vessel and stirred rapidly. A gram of the first monomer represented by formula (1) is first added, reacted for 4 to 18 hours, then b gram of the monomer represented by formula (2) is added, reacted for 4 to 18 hours, and finally c gram of the second monomer represented by formula (1) is added, reacted for 4 to 18 hours, and then the block copolymer is obtained. The first monomer represented by formula (1) and the second monomer represented by formula (1) may be the same or different, and a, b, c satisfy the following relationship: (b / (a+b+c))×100%=55% to 90%.

[0080] The solvent in the above step can be, for example but not limited to, a polar solvent (such as tetrahydrofuran) or a non-polar solvent (such as cyclohexane), preferably tetrahydrofuran.

[0081] The anionic initiator in the above step may be, for example but not limited to, n-butyl lithium or tert-butyl lithium, preferably n-butyl lithium.

[0082] The inert atmosphere in the above steps may be, for example but not limited to, an argon atmosphere or a nitrogen atmosphere, preferably an argon atmosphere.

[0083] 2. A copolymer having a structural unit formed from a monomer represented by formula (1) and a structural unit formed from a monomer represented by formula (2) is a random copolymer.

[0084] At 20°C to 70°C, a solvent and a mixture of the monomer represented by formula (1) and the monomer represented by formula (2) (wherein the mass content of the monomer represented by formula (2) in the mixture is 55wt% to 90wt%, and the total molar amount of the mixture is d moles) are added to a reaction container, stirred evenly, and a cationic initiator (molar amount is e moles) is continuously added, and the reaction is performed for 4 to 72 hours to obtain a random copolymer having a structural unit content of 55wt% to 90wt% formed by the monomer represented by formula (2). d and e satisfy the following relationship: (e / d)×100%=0.5%~2%.

[0085] The solvent in the above steps may be, for example but not limited to, n-propyl acetate, n-butyl acetate or tetrahydrofuran, preferably n-propyl acetate.

[0086] The cationic initiator in the above step can be, for example but not limited to, boron trifluoride diethyl ether, boron trifluoride methyl ether or aluminum trichloride, preferably boron trifluoride diethyl ether.

[0087] In the present invention, the compound represented by formula (3) is a cyclic phosphazene compound containing a P=N bond in its structure, wherein n represents the number of P=N bonds, and n is an integer from 3 to 6. In other words, when n is 3, the compound represented by formula (3) is a cyclic phosphazene having a six-membered ring, and when n is 6, the compound represented by formula (3) is a cyclic phosphazene having a twelve-membered ring. In addition, the phosphorus atom in the cyclic phosphazene structure of the compound represented by formula (3) can be substituted by an o-vinylphenoxy group, an m-vinylphenoxy group, or a p-vinylphenoxy group.

[0088] In the present invention, for example, when n is 3, the sum of the numbers of o-vinylphenoxy, m-vinylphenoxy and p-vinylphenoxy groups in the cyclic phosphazene structure of the compound represented by formula (3) is 6, the number of o-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5 or 6, the number of m-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5 or 6, and the number of p-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5 or 6. For example, when n is 3, the number of o-vinylphenoxy groups in the cyclic phosphazene structure of the compound represented by formula (3) is 0, the number of p-vinylphenoxy groups is 6, and the number of m-vinylphenoxy groups is 0. For example, when n is 3, the number of o-vinylphenoxy groups in the cyclic phosphazene structure of the compound represented by formula (3) is 6, the number of p-vinylphenoxy groups is 0, and the number of m-vinylphenoxy groups is 0. For example, when n is 3, the number of o-vinylphenoxy groups in the cyclic phosphazene structure of the compound represented by formula (3) is 3, the number of p-vinylphenoxy groups is 2, and the number of m-vinylphenoxy groups is 1. For example, when n is 6, the sum of the numbers of o-vinylphenoxy groups, m-vinylphenoxy groups and p-vinylphenoxy groups in the cyclic phosphazene structure of the compound represented by formula (3) is 12, wherein the number of o-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, the number of m-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, and the number of p-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12.

[0089] For example, in one embodiment, the compound represented by formula (3) includes any one or a combination of the compound represented by formula (3-1) to the compound represented by formula (3-14),

[0090]

[0091]

[0092]

[0093] In the present invention, unless otherwise specified, the pH value of the compound represented by formula (3) is not particularly limited, and is preferably 5 to 10, such as but not limited to 5, 6, 7, 8, 9 or 10. The pH value of the compound can be measured by a measuring instrument known in the art, such as but not limited to a pH meter, or, for example, by titration using an acid-base titration method. For example, in one embodiment, the compound represented by formula (3) and deionized water with a pH value of 7 are mixed in a weight ratio of 1:10, the mixed solution is filtered and extracted at room temperature, and the pH value of the extract is measured using a pH meter to obtain the pH value of the compound represented by formula (3). When measured by a pH meter, the pH value of the compound represented by formula (3) may also be a small value, such as but not limited to 5.5, 6.5 or 7.3, and is not limited thereto.

[0094] In the present invention, unless otherwise specified, the compound represented by formula (3) can be prepared by various methods known to those skilled in the art.

[0095] For example, the compound represented by formula (3) can be prepared by the following method:

[0096] Step (1): reacting chlorinated cyclophosphazene with hydroxybenzaldehyde (o-hydroxybenzaldehyde and / or m-hydroxybenzaldehyde and / or p-hydroxybenzaldehyde) to obtain an intermediate product; and

[0097] Step (2): reacting the intermediate product with methyltriphenylphosphonium bromide in the presence of a catalytic base to obtain a compound represented by formula (3).

[0098] In step (1), an acid binding agent may be further added as needed, and the acid binding agent includes but is not limited to potassium carbonate, triethylamine or a combination thereof.

[0099] In step (1), an organic solvent may be further added as needed, and the organic solvent includes but is not limited to tetrahydrofuran. Unless otherwise specified, the tetrahydrofuran used in the present invention is tetrahydrofuran from which water has been removed (anhydrous tetrahydrofuran).

[0100] In step (1), the chlorinated cyclophosphazene includes but is not limited to hexachlorocyclotriphosphazene, octachlorocyclotetraphosphazene, decachlorocyclopentaphosphazene, dodecachlorocyclohexaphosphazene or a combination thereof. For example, the molar ratio of the chlorinated cyclophosphazene to hydroxybenzaldehyde is 1:6 to 1:12.

[0101] In step (1), for example, the reaction temperature after adding o-hydroxybenzaldehyde, m-hydroxybenzaldehyde or p-hydroxybenzaldehyde is 40 to 70° C., and the reaction time is 24 to 96 hours, preferably 48 to 72 hours.

[0102] In step (2), the catalytic base includes but is not limited to potassium tert-butoxide, sodium methoxide or a combination thereof; for example, the reaction temperature after adding the catalytic base is 25 to 50° C., and the reaction time is 1 to 6 hours, preferably 2 to 3 hours.

[0103] In step (2), an organic solvent may be further added as needed, and the organic solvent includes but is not limited to tetrahydrofuran from which water has been removed.

[0104] In step (2), calcium bromide may be added as needed. The reaction temperature after adding calcium bromide is 25 to 50° C., and the reaction time is 12 to 72 hours, preferably 24 to 48 hours.

[0105] In step (2), for example, the pH value of the reaction system can be adjusted to 3 to 13 by using an aqueous acetic acid solution or an aqueous ammonium chloride solution.

[0106] For example, in one embodiment, the resin composition of the present invention further comprises a cross-linking agent containing unsaturated carbon-carbon double bonds. For example, relative to 100 parts by weight of the copolymer, the resin composition of the present invention may contain 1 to 30 parts by weight of the cross-linking agent containing unsaturated carbon-carbon double bonds, preferably 2 to 10 parts by weight of the cross-linking agent containing unsaturated carbon-carbon double bonds.

[0107] The cross-linking agent containing unsaturated carbon-carbon double bonds applicable to the present invention refers to a difunctional or higher molecular compound containing unsaturated carbon-carbon double bonds having a molecular weight less than or equal to 1000, and the molecular weight is preferably between 100 and 900, and more preferably between 100 and 800. For example, the cross-linking agent containing unsaturated carbon-carbon double bonds is any one of bis(vinylphenyl)ethane (BVPE), divinylbenzene (DVB), divinylnaphthalene, divinylbiphenyl, triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), vinylbenzocyclobutene (VBCB), di(vinylbenzyl)ether (BVBE), trivinylcyclohexane (TVCH), diallylbisphenol A (DABPA), difunctional or higher acrylate, butadiene, decadiene and octadiene, or a combination thereof.

[0108] The difunctional or higher acrylate includes various difunctional acrylates, trifunctional acrylates or tetrafunctional or higher acrylates known in the art, and can be purchased from Shin-Nakamura Chemical Industry Co., Ltd., Kyoeisha Chemical Co., Ltd., Nippon Kayaku Co., Ltd. or Sartomer Co., Ltd. Specific examples include but are not limited to any one of diallyl isophthalate (DAIP), dioxanediol diacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate or a combination thereof.

[0109] For example, in one embodiment, the resin composition of the present invention may further include any one of a polyolefin different from the copolymer, a polyphenylene ether resin containing unsaturated carbon-carbon double bonds, a benzoxazine resin, an epoxy resin, a polyester resin, a phenol resin, an amine curing agent, a polyamide, a polyimide, styrene maleic anhydride, a maleimide resin, a cyanate ester, and a maleimide triazine resin, or a combination thereof as needed.

[0110] For example, in one embodiment, the resin composition of the present invention further comprises a polyolefin different from the copolymer. For example, relative to 100 parts by weight of the copolymer, the resin composition of the present invention may contain 1 to 50 parts by weight of a polyolefin different from the copolymer, preferably 2 to 10 parts by weight of a polyolefin different from the copolymer.

[0111] In the present invention, for example, the polyolefin different from the copolymer suitable for the present invention is not particularly limited, except that it is different from the copolymer and can be any one or more polyolefins suitable for preparing prepregs, resin films, laminates or printed circuit boards, and can be any one or more commercially available products, homemade products or combinations thereof. For example, the polyolefin different from the copolymer suitable for the present invention includes but is not limited to diene polymers, monoene polymers, hydrogenated diene polymers or combinations thereof. The diene refers to a hydrocarbon compound containing two unsaturated carbon-carbon double bonds in the molecule, and the monoene refers to a hydrocarbon compound containing one unsaturated carbon-carbon double bond in the molecule. The polyolefins different from the copolymers suitable for the present invention include, for example, but are not limited to, polybutadiene, polyisoprene, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-butadiene-divinylbenzene terpolymer, styrene-butadiene-maleic anhydride terpolymer, vinyl-polybutadiene-urea polymer, maleic anhydride-butadiene copolymer, polymethylstyrene, hydrogenated polybutadiene, hydrogenated polyisoprene, hydrogenated styrene-butadiene-divinylbenzene terpolymer, hydrogenated styrene-butadiene-maleic anhydride terpolymer, hydrogenated styrene-butadiene copolymer, hydrogenated styrene-isoprene copolymer, and any one or a combination of multifunctional vinyl aromatic copolymers. For example, if not specifically indicated, the multifunctional vinyl aromatic copolymers used in the present invention may include various types of multifunctional vinyl aromatic copolymers disclosed in U.S. Patent No. US20070129502A1, all of which are incorporated herein by reference.

[0112] For example, in one embodiment, the resin composition of the present invention further comprises a polyphenylene ether resin containing unsaturated carbon-carbon double bonds. For example, relative to 100 parts by weight of the copolymer, the resin composition of the present invention may contain 1 to 50 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, preferably 2 to 10 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds.

[0113] In the present invention, for example, the polyphenylene ether resin containing unsaturated carbon-carbon double bonds suitable for the present invention is not particularly limited, and can be any one or more polyphenylene ether resins containing unsaturated carbon-carbon double bonds suitable for preparing prepregs, resin films, laminates or printed circuit boards, and can be any one or more commercially available products, homemade products or combinations thereof, such as but not limited to any one or a combination of vinylbenzyl polyphenylene ether resins, (meth)acryl polyphenylene ether resins and vinyl polyphenylene ether resins.

[0114] The polyphenylene ether resin containing unsaturated carbon-carbon double bonds of the present invention has unsaturated carbon-carbon double bonds and a phenylene ether skeleton, wherein the unsaturated carbon-carbon double bonds are reactive functional groups, which can self-polymerize after being heated, and can also undergo free radical polymerization reaction with other unsaturated bond-containing components in the resin composition and finally crosslink and cure. Preferably, the polyphenylene ether resin containing unsaturated carbon-carbon double bonds includes a polyphenylene ether resin containing unsaturated carbon-carbon double bonds substituted with 2,6-dimethyl on the phenylene ether skeleton, and the methyl groups after substitution form a steric hindrance so that the oxygen atoms on the ether are not easy to generate hydrogen bonds or van der Waals forces and absorb moisture.

[0115] For example, in one embodiment, the polyphenylene ether resin containing unsaturated carbon-carbon double bonds includes, but is not limited to, vinylbenzyl polyphenylene ether resin having a number average molecular weight of about 1200 (e.g., OPE-2st 1200, available from Mitsubishi Gas Chemical Co., Ltd.), vinylbenzyl polyphenylene ether resin having a number average molecular weight of about 2200 (e.g., OPE-2st 2200, available from Mitsubishi Gas Chemical Co., Ltd.), vinylbenzyl polyphenylene ether resin having a number average molecular weight of about 2400 to 2800 (e.g., vinylbenzyl bisphenol A polyphenylene ether resin), (meth)acryl polyphenylene ether resin having a number average molecular weight of about 1900 to 2300 (e.g., SA9000, available from Sabic), vinyl polyphenylene ether resin having a number average molecular weight of about 2200 to 3000, or a combination thereof. The vinyl polyphenylene ether resin may include various types of polyphenylene ether resins disclosed in U.S. Patent Application US20160185904A1, all of which are incorporated herein by reference. For example, in one embodiment, the vinylbenzyl polyphenylene ether resin includes, but is not limited to, vinylbenzyl biphenyl polyphenylene ether resin, vinylbenzyl bisphenol A polyphenylene ether resin, or a combination thereof.

[0116] If not otherwise specified, in the resin composition of the present invention, the amount of benzoxazine resin, epoxy resin, polyester resin, phenol resin, polyamide, polyimide, styrene maleic anhydride, maleimide resin, cyanate ester, maleimide triazine resin is not particularly limited relative to 100 parts by weight of the copolymer, for example, it can be 1 to 100 parts by weight, for example, but not limited to 1 part by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 50 parts by weight or 100 parts by weight. The amount of amine curing agent relative to 100 parts by weight of the copolymer is also not particularly limited, for example, it can be 1 to 15 parts by weight, for example, but not limited to 1 part by weight, 4 parts by weight, 7.5 parts by weight, 12 parts by weight or 15 parts by weight.

[0117] In the present invention, for example, the benzoxazine resin may be any type of benzoxazine resin known in the art. Specific examples include, but are not limited to, bisphenol A benzoxazine resin, bisphenol F benzoxazine resin, phenolphthalein benzoxazine resin, dicyclopentadiene benzoxazine resin, phosphorus-containing benzoxazine resin, diamino benzoxazine resin, and phenyl, vinyl or allyl modified benzoxazine resin or a combination thereof. Suitable commercially available products include, for example, Huntsman sold under the trade names LZ-8270 (phenolphthalein benzoxazine resin), LZ-8298 (phenolphthalein benzoxazine resin), LZ-8280 (bisphenol F benzoxazine resin), LZ-8290 (bisphenol A benzoxazine resin), or sold under the trade names KZH-5031 (vinyl modified benzoxazine resin), KZH-5032 (phenyl modified benzoxazine resin) by Kolon Industries of Korea. The diaminobenzoxazine resin may be diaminodiphenylmethane benzoxazine resin, diaminodiphenyl ether benzoxazine resin, diaminodiphenyl sulfone benzoxazine resin, diaminodiphenyl sulfide benzoxazine resin or a combination thereof, and is not limited thereto.

[0118] In the present invention, for example, the epoxy resin can be various epoxy resins known in the art. From the perspective of improving the heat resistance of the resin composition, the epoxy resin includes, but is not limited to, for example, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AD ​​epoxy resin, novolac epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, multifunctional novolac epoxy resin, dicyclopentadiene (DCPD) epoxy resin, phosphorus-containing epoxy resin, p-xylene epoxy resin, naphthalene epoxy resin (e.g., naphthol epoxy resin), benzofuran epoxy resin, isocyanate-modified epoxy resin, any one or a combination thereof. In the present invention, for example, the novolac epoxy resin may be phenol novolac epoxy resin, bisphenol Anovolac epoxy resin, bisphenol F novolac epoxy resin, biphenylnovolac epoxy resin, phenol benzaldehyde epoxy resin, phenolaralkyl novolac epoxy resin or o-cresol novolac epoxy resin. In the present invention, for example, the phosphorus-containing epoxy resin may be DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) epoxy resin, DOPO-HQ epoxy resin or a combination thereof. The DOPO epoxy resin may be selected from one or more of DOPO-containing phenol novolac epoxy resin, DOPO-containing o-cresol novolac epoxy resin and DOPO-containing bisphenol-A novolac epoxy resin.The DOPO-HQ epoxy resin may be selected from one or more of DOPO-HQ-containing phenol novolacepoxy resin, DOPO-HQ-containing o-cresol novolac epoxy resin, and DOPO-HQ-containing bisphenol-A novolac epoxy resin, and is not limited thereto.

[0119] In the present invention, for example, the polyester resin may be any polyester resin known in the art. Specific examples include, but are not limited to, polyester resins containing a dicyclopentadiene structure and polyester resins containing a naphthalene ring structure or a combination thereof. Specific examples include, but are not limited to, the trade names HPC-8000 or HPC-8150 sold by Dainippon Ink Chemicals.

[0120] In the present invention, for example, the phenol resin may be any phenol resin known in the art. Specific examples include, but are not limited to, phenolic resin or phenoxy resin, wherein the phenolic resin includes at least one of phenolic resin, o-methylphenolic resin, bisphenol A resin, naphthol resin, biphenyl phenolic resin and dicyclopentadiene phenol resin or a combination thereof, and is not limited thereto.

[0121] In the present invention, for example, the amine curing agent may be any amine curing agent known in the art, and specific examples include but are not limited to at least one of diaminodiphenyl sulfone, diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfide and dicyandiamide, or a combination thereof.

[0122] In the present invention, for example, the polyamide may be any of various polyamides known in the art, and specific examples include but are not limited to various commercially available polyamide resin products.

[0123] In the present invention, for example, the polyimide may be any polyimide known in the art, and specific examples include but are not limited to various commercially available polyimide resin products.

[0124] In the present invention, for example, styrene maleic anhydride can be various styrene maleic anhydride known in the art, wherein the ratio of styrene (St) to maleic anhydride (MA) can be 1 / 1, 2 / 1, 3 / 1, 4 / 1, 6 / 1, 8 / 1 or 12 / 1. Specific examples include, but are not limited to, styrene maleic anhydride copolymers sold by Cray Valley under the trade names SMA-1000, SMA-2000, SMA-3000, EF-30, EF-40, EF-60 and EF-80, or styrene maleic anhydride copolymers sold by Polyscope under the trade names C400, C500, C700, C900, etc.

[0125] In the present invention, for example, the maleimide resin may be any of various maleimide resins known in the art. Specific examples include, but are not limited to: 4,4'-diphenylmethanebismaleimide, polyphenylmethane maleimide (or oligomer of phenylmethane maleimide), bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethanebismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethanebismaleimide, 3,3'-dimethyl-5,5'-dipropyl-4,4'-diphenylmethane bismaleimide), 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, N-2,3-xylylmaleimide, N-2,6-xylylmaleimide, N-phenylmaleimide, vinyl benzyl maleimide The present invention also includes maleimide, biphenyl maleimide, maleimide resin containing aliphatic structure with carbon number of 10 to 50, maleimide containing indane structure, maleimide containing meta-arylene structure, prepolymer of diallyl compound and maleimide resin, prepolymer of diamine and maleimide resin, prepolymer of multifunctional amine and maleimide resin, prepolymer of acidic phenol compound and maleimide resin or a combination thereof. When reading, it should also be understood to include modified substances of these components.

[0126] For example, the maleimide resins include, but are not limited to, maleimide resins produced by Daiwakasei Industry with trade names such as BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-2000, BMI-2300, BMI-3000, BMI-3000H, BMI-4000, BMI-5000, BMI-5100, BMI-TMH, BMI-7000 and BMI-7000H, or maleimide resins produced by KI Chemical Co., Ltd. with trade names such as BMI-70 and BMI-80, or maleimide resins produced by Nippon Kayaku Co., Ltd. with trade names such as MIR-3000 and MIR-5000.

[0127] For example, the maleimide resin containing an aliphatic structure with 10 to 50 carbon atoms, or the maleimide resin extended by imide, may include various maleimide resins extended by imide disclosed in Taiwan Patent Application Publication No. TW200508284A, all of which are incorporated herein by reference. The maleimide resin containing an aliphatic structure with 10 to 50 carbon atoms suitable for the present invention is, for example, but not limited to, the maleimide resin produced by the designer molecular company under the trade names of BMI-689, BMI-1400, BMI-1500, BMI-1700, BMI-2500, BMI-3000, BMI-5000 and BMI-6000.

[0128] In the present invention, for example, the cyanate ester may be various cyanate resins known in the art, such as compounds having an Ar-OC≡N structure, wherein Ar may be a substituted or unsubstituted aromatic group. From the perspective of improving the heat resistance of the resin composition, specific examples include, but are not limited to, phenolic cyanate resins, bisphenol A cyanate resins, bisphenol F cyanate resins, cyanate resins containing dicyclopentadiene structures, cyanate resins containing naphthalene ring structures, phenolphthalein cyanate resins, adamantane cyanate resins, fluorene cyanate resins, or combinations thereof. Among them, the phenolic cyanate resin may be a bisphenol A phenolic cyanate resin, a bisphenol F phenolic cyanate resin, or a combination thereof. For example, the cyanate resin may be a cyanate resin produced by Lonza under the trade names of Primaset PT-15, PT-30S, PT-60S, BA-200, BA-230S, BA-3000S, BTP-2500, BTP-6020S, DT-4000, DT-7000, ULL950S, HTL-300, CE-320, LVT-50, LeCy, etc.

[0129] In the present invention, for example, the maleimide triazine resin may be various maleimide triazine resins known in the art. Specific examples include, but are not limited to: maleimide triazine resins obtained by polymerizing maleimide resins with bisphenol A type cyanate resins, maleimide triazine resins obtained by polymerizing maleimide resins with bisphenol F type cyanate resins, maleimide triazine resins obtained by polymerizing maleimide resins with phenol novolac type cyanate resins, and maleimide triazine resins obtained by polymerizing maleimide resins with cyanate resins containing dicyclopentadiene structures. In one embodiment, the maleimide triazine resin may be obtained by polymerizing the aforementioned maleimide resin and the aforementioned cyanate resin in any molar ratio. For example, the molar ratio of maleimide resin to cyanate resin may be 1:1 to 1:10, such as but not limited to 1:1, 1:2, 1:4, 1:6.

[0130] For example, in one embodiment, the resin composition further comprises any one or a combination of an inorganic filler, a flame retardant different from the compound represented by formula (3), a hardening accelerator, an inhibitor, a solvent, a silane coupling agent, a colorant, and a toughening agent.

[0131] In the present invention, for example, the inorganic filler can be any one or more inorganic fillers suitable for preparing prepregs, resin films, laminates or printed circuit boards, and specific examples thereof include, but are not limited to, silicon dioxide (molten, non-molten, porous or hollow), aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, barium titanate, lead titanate, strontium titanate, calcium titanate, magnesium titanate, barium zirconate, lead zirconate, magnesium zirconate, lead zirconate titanate, zinc molybdate, calcium molybdate, magnesium molybdate, ammonium molybdate, zinc molybdate-modified talc, zinc oxide, zirconium oxide, mica, boehmite (AlOOH), calcined talc, talc, silicon nitride, zirconium tungstate, petalite, calcined kaolin or a combination thereof. In addition, the inorganic filler may be spherical (including solid spherical or hollow spherical), fibrous, plate-like, granular, flaky or needle-like, and may be selectively pretreated with a silane coupling agent. For example, in one embodiment, relative to 100 parts by weight of the copolymer, the resin composition of the present invention may further include 10 to 300 parts by weight of the inorganic filler, preferably 50 to 300 parts by weight of the inorganic filler, more preferably 80 to 200 parts by weight of the inorganic filler, but is not limited thereto.

[0132] In the present invention, for example, the flame retardant different from the compound represented by formula (3) may be any one or more other flame retardants suitable for preparing semi-cured sheets, resin films, laminates or printed circuit boards, such as but not limited to phosphorus-containing flame retardants or bromine-containing flame retardants. The bromine-containing flame retardant preferably includes decabromodiphenylethane, and the phosphorus-containing flame retardant preferably includes hydroquinone bis-(diphenyl phosphate), bisphenol A bis-(diphenyl phosphate), tri(2-carboxyethyl)phosphine (TCEP), tri(chloroisopropyl) phosphate, trimethyl phosphate (TMP), dimethyl methyl phosphonate (DMMP), resorcinol bis(dixylenyl phosphate), RDXP (such as commercial products such as PX-200, PX-201, PX-202), ammonium polyphosphate, melamine polyphosphate, DPPO (diphenylphosphine oxide and its derivatives (such as bis-DPPO compounds) or resins, melamine cyanurate and tri-hydroxy ethyl isocyanurate, aluminum phosphinate (such as OP-930, OP-935 and other products) or combinations thereof.

[0133] For example, in one embodiment, the flame retardant can be a flame retardant sold by Katayama Chemical Industry Co., Ltd., such as but not limited to V1, V2, V3, V4, V5, V7, S-2, S-4, E-4c, E-7c, E-8g, E-9g, E-10g, E-100, B-3, W-1o, W-2h, W-2o, W-3o, W-4o, OX-1, OX-2, OX-4, OX-6, OX-6+, OX-7, OX-7+, OX-13, BPE-1, BPE-3, HyP-2, API-9, CMPO, ME-20, C-1R, C-1S, C-3R, C-3S or C-11R. The flame retardant of the present invention can include one or more of the above.

[0134] The present invention preferably includes a phosphate flame retardant, for example including but not limited to resorcinol bis(bis-xylyl phosphate) or its polycondensate, a phosphate containing an unsaturated carbon-carbon double bond or a combination thereof.

[0135] The phosphate containing unsaturated carbon-carbon double bonds of the present invention includes the structure shown in P1 below:

[0136]

[0137] Wherein, A is independently an alkyl group having 1 to 3 carbon atoms, and B is a functional group containing an unsaturated carbon-carbon double bond, preferably, B is vinyl, vinylbenzyl, allyl or butadienyl. Specific examples of the phosphate containing an unsaturated carbon-carbon double bond include, but are not limited to, flame retardants sold by Katayama Chemical Industry Co., Ltd. under the trade names of S-2, V2, and B-3.

[0138] For example, in one embodiment, relative to 100 parts by weight of the copolymer, the resin composition of the present invention may further include 1 to 15 parts by weight of a phosphate flame retardant, preferably 2 to 10 parts by weight of a phosphate flame retardant.

[0139] For example, in one embodiment, the weight ratio of the compound represented by formula (3) to the phosphate flame retardant is between 4:1 and 11:1. For example, but not limited to, the weight ratio of the compound represented by formula (3) to the phosphate flame retardant is 4:1, 5.5:1, 6.6:1, 7:1, 8:1, 9:1, 10:1 or 11:1. The use of the compound represented by formula (3) and the phosphate flame retardant can further improve the dielectric aging properties of the product.

[0140] In the present invention, for example, the hardening accelerator may include a catalyst such as a Lewis base or a Lewis acid. Among them, the Lewis base may include one or more of imidazole, boron trifluoride amine complex, ethyltriphenyl phosphonium chloride, 2-methylimidazole (2MI), 2-phenyl-1H-imidazole (2PZ), 2-ethyl-4-methylimidazole (2E4MZ), triphenylphosphine (TPP) and 4-dimethylaminopyridine (DMAP). The Lewis acid may include a metal salt compound, such as a metal salt compound of manganese, iron, cobalt, nickel, copper, zinc, etc., such as a metal catalyst such as zinc octanoate and cobalt octanoate. The hardening accelerator also includes a hardening initiator, such as a peroxide that can generate free radicals. The hardening initiator includes, but is not limited to, diisopropylbenzene peroxide (DCP), tert-butyl peroxybenzoate, dibenzoyl peroxide (BPO), 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne (25B) and bis(tert-butylperoxyisopropyl)benzene or a combination thereof. For example, in one embodiment, the resin composition of the present invention may further include 0.001 to 5 parts by weight of a hardening accelerator, preferably 0.01 to 3.5 parts by weight of a hardening accelerator, and more preferably 0.1 to 2.0 parts by weight of a hardening accelerator, relative to 100 parts by weight of the copolymer, but is not limited thereto.

[0141] In the present invention, for example, the inhibitor may include but is not limited to 1,1-diphenyl-2-trinitrophenylhydrazine, methacrylonitrile, nitrogen oxide stable free radicals, triphenylmethyl free radicals, metal ion free radicals, sulfur free radicals (for example, including but not limited to dithioesters), hydroquinone, p-methoxyphenol, p-benzoquinone, phenothiazine, β-phenylnaphthylamine, p-tert-butylcatechol, methylene blue, 4,4'-butylenebis(6-tert-butyl-3-methylphenol) and 2,2'-methylenebis(4-ethyl-6-tert-butylphenol) or a combination thereof. For example, the above-mentioned nitrogen oxide stable free radicals may include but are not limited to nitrogen oxide free radicals from cyclic hydroxylamines such as 2,2,6,6-tetramethyl-1-oxy-piperidine, 2,2,6,6-substituted-1-piperidinyloxy free radicals or 2,2,5,5-substituted-1-pyrrolidinyloxy free radicals. As a substituent, an alkyl group with a carbon number of less than four, such as a methyl group or an ethyl group, is preferred. Specific nitrogen oxide free radical compounds are not limited, and examples include but are not limited to 2,2,6,6-tetramethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetraethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetramethyl-4-oxo-1-piperidinyloxy free radicals, 2,2,5,5-tetramethyl-1-pyrrolidinyloxy free radicals, 1,1,3,3-tetramethyl-2-isoindolinyloxy free radicals, N,N-di-tert-butylamineoxy free radicals, etc. Stable free radicals such as galvinoxyl free radicals can also be used to replace nitrogen oxide free radicals. The inhibitor suitable for the resin composition of the present invention can also be a product derived from the hydrogen atom or atomic group in the inhibitor being replaced by other atoms or atomic groups. For example, the hydrogen atom in the inhibitor is replaced by an atomic group such as an amino group, a hydroxyl group, a ketocarbonyl group, etc. For example, in one embodiment, the resin composition of the present invention may further include 0.001 to 20 parts by weight of a polymerization inhibitor, preferably 0.001 to 10 parts by weight of a polymerization inhibitor, relative to 100 parts by weight of the copolymer, but is not limited thereto.

[0142] In the present invention, for example, the solvent can be any solvent suitable for dissolving the resin composition of the present invention, including but not limited to: methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone (also known as methyl ethyl ketone), methyl isobutyl ketone, cyclohexanone, nitrogen methyl pyrrolidone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, dimethylformamide, dimethylacetamide, propylene glycol methyl ether acetate and other solvents or mixed solvents thereof. The amount of solvent added is to be able to completely dissolve the resin and adjust to a specific total solid content of the resin composition. For example, in one embodiment, the amount of solvent added is added to adjust the total solid content of the resin composition to 50wt% to 85wt%, but is not limited thereto.

[0143] In the present invention, for example, the silane coupling agent may include a silane compound (silane, for example, including but not limited to a siloxane compound), which may be further divided into an aminosilane compound, an epoxysilane compound, a vinylsilane compound, a hydroxysilane compound, an isocyanate silane compound, a methacryloxysilane compound, and an acryloxysilane compound according to the type of functional group. For example, in one embodiment, relative to 100 parts by weight of the copolymer, the resin composition of the present invention may further include 0.001 to 20 parts by weight of a silane coupling agent, preferably 0.01 to 10 parts by weight of a silane coupling agent, but is not limited thereto.

[0144] In the present invention, for example, the coloring agent may include but is not limited to a dye or a pigment. For example, in one embodiment, relative to 100 parts by weight of the copolymer, the resin composition of the present invention may further include 0.001 parts by weight to 10 parts by weight of the coloring agent, preferably 0.01 parts by weight to 5 parts by weight of the coloring agent, but is not limited thereto.

[0145] In the present invention, the main function of adding a toughening agent is to improve the toughness of the resin composition. For example, the toughening agent suitable for the present invention may include, but is not limited to, carboxyl-terminated butadieneacrylonitrile rubber (CTBN), core-shell rubber, ethylene-propylene rubber and other compounds or combinations thereof. For example, in one embodiment, relative to 100 parts by weight of the copolymer, the resin composition of the present invention may further include 1 to 20 parts by weight of a toughening agent, preferably 3 to 10 parts by weight of a toughening agent, but is not limited thereto.

[0146] The present invention also provides a product made of the resin composition, such as a component suitable for various electronic products, including but not limited to a prepreg, a resin film, a laminate or a printed circuit board.

[0147] For example, the resin composition of the present invention can be made into a semi-cured sheet, which includes a reinforcing material and a layered object arranged on the reinforcing material. The layered object is obtained by heating the aforementioned resin composition at a high temperature to form a semi-cured state (B-stage). The baking temperature for making the semi-cured sheet is between 120°C and 180°C, preferably between 120°C and 160°C. The reinforcing material can be any one of a fiber material, a woven fabric, and a non-woven fabric, and the woven fabric preferably includes a glass fiber cloth. The type of glass fiber cloth is not particularly limited, and can be various glass fiber cloths that can be used for printed circuit boards, such as E-type glass cloth, D-type glass cloth, S-type glass cloth, T-type glass cloth, L-type glass cloth, Q-type glass cloth or QL-type glass cloth (a glass cloth of a mixed structure made of Q glass and L glass); the types of glass fibers include yarns and rovings, etc., and the forms include open fiber or unopen fiber, and the end face shape includes a circular or flat shape. The aforementioned non-woven fabric preferably includes a liquid crystal resin non-woven fabric, such as a polyester non-woven fabric, a polyurethane non-woven fabric, etc., and is not limited thereto. The aforementioned fabric may also include a liquid crystal resin fabric, such as a polyester fabric or a polyurethane fabric, etc., and is not limited thereto. This reinforcing material can increase the mechanical strength of the prepreg. In a preferred embodiment, the reinforcing material can also be selectively pretreated with a silane coupling agent. The prepreg is subsequently heated and cured (C-stage) to form an insulating layer.

[0148] For example, the resin composition of the present invention can be made into a resin film, which is obtained by semi-curing the aforementioned resin composition after baking and heating. The resin composition can be selectively coated on a liquid crystal resin film, a polytetrafluoroethylene film, a polyethylene terephthalate film (PET film), a polyimide film (PI film), a copper foil or a copper foil with adhesive, and then semi-cured by baking and heating to form a resin film.

[0149] For example, the resin composition described in the present invention can be made into various laminates, which include at least two metal foils and at least one insulating layer, wherein the insulating layer is disposed between the two metal foils, and the insulating layer can be formed by curing the aforementioned resin composition under high temperature and high pressure (C-stage), and the applicable curing temperature is, for example, between 190°C and 220°C, preferably between 200°C and 210°C, and the curing time is 90 to 180 minutes, preferably 120 to 150 minutes. The aforementioned insulating layer can be obtained by curing the aforementioned semi-cured sheet or resin film. The material of the aforementioned metal foil can be copper, aluminum, nickel, platinum, silver, gold or their alloys, such as copper foil. In a preferred embodiment, the laminate is a copper foil substrate.

[0150] In one embodiment, the aforementioned laminate can be further processed into a printed circuit board after circuit processing. One method of making the printed circuit board of the present invention can be to use a double-sided copper-clad laminate (such as product EM-827, which can be purchased from Taiwan Optoelectronics Materials) with a thickness of 28 mils and 1 ounce of HTE (High Temperature Elongation) copper foil, and electroplating after drilling to form electrical conduction between the upper copper foil and the bottom copper foil. The upper copper foil and the bottom copper foil are then etched to form an inner layer circuit. The inner layer circuit is then browned and roughened to form a concave-convex structure on the surface to increase the roughness. Then, the copper foil, the aforementioned prepreg, the aforementioned inner layer circuit board, the aforementioned prepreg, and the copper foil are stacked in sequence, and then a vacuum laminating device is used to heat for 90 to 180 minutes at a temperature of 190°C to 220°C to cure the insulating layer material of the prepreg. Next, various circuit board processing techniques known in the art such as blackening, drilling, and copper plating are performed on the copper foil on the outermost surface to obtain a printed circuit board.

[0151] For example, in one embodiment, the resin composition disclosed in the present invention and various products prepared therefrom preferably have one or more of the following characteristics:

[0152] The reflow soldering warpage measured according to the Full-field Signed Warpage test method is less than or equal to 10 μm, for example, between 6 μm and 10 μm;

[0153] The Z-axis thermal expansion rate measured according to the method of IPC-TM-650 2.4.24.5 is less than or equal to 1.0%, such as between 0.5% and 1.0%;

[0154] The product was tested for heat resistance of multilayer boards and no board explosion occurred;

[0155] After standing at a constant temperature of 125° C. for 240 hours, the dielectric loss aging rate calculated by the dielectric loss measured at a frequency of 10 GHz according to the method of JIS C2565 is less than or equal to 60%, for example, between 38% and 60%;

[0156] The dielectric constant temperature coefficient measured according to the method of IPC-TM-650 2.5.5.13 is less than or equal to 70 ppm / °C, for example, between 48.7 ppm / °C and 68.7 ppm / °C;

[0157] The dielectric loss temperature coefficient measured according to the method of IPC-TM-650 2.5.5.13 is less than or equal to 4000 ppm / °C, for example, between 2582 ppm / °C and 3999 ppm / °C.

[0158] The resin compositions of the embodiments and comparative examples of the present invention were prepared using various raw materials from the following sources and in the amounts shown in Tables 1 to 5, and were further made into various test samples.

[0159] The chemical raw materials used in the embodiments of the present invention and the comparative examples are as follows:

[0160] Copolymers A1-A11 and B1-B4: See Synthesis Examples 1-12. Among them, copolymers A1-A11 are copolymers of the present invention (having structural units formed by monomers represented by formula (1) and structural units formed by monomers represented by formula (2), and the content of structural units formed by monomers represented by formula (2) in the copolymers is 55wt% to 90wt%); in copolymers B1 and B2, the content of structural units formed by monomers represented by formula (2) in the copolymers is not within the range of 55wt% to 90wt%; copolymer B3 is a homopolymer of the monomer represented by formula (2), and is therefore placed under the column of copolymers for the convenience of parallel comparison; copolymer B4 does not have structural units formed by monomers represented by formula (2).

[0161] The compound represented by formula (3-1): synthesized by oneself, see Synthesis Example 13.

[0162] The compound represented by formula (3-2): synthesized by oneself, see Synthesis Example 14.

[0163] The compound represented by formula (3-4): synthesized by oneself, see Synthesis Example 15.

[0164] The compound represented by formula (3-9): synthesized by oneself, see Synthesis Example 16.

[0165] B-3000: polybutadiene, purchased from Nippon Soda.

[0166] Ricon 100: Styrene-butadiene copolymer, available from Cray Valley.

[0167] SBS-A: styrene-butadiene-styrene triblock copolymer, purchased from Japan Soda.

[0168] H-1051: Hydrogenated polybutadiene-styrene copolymer, available from Asahi Kasei Co.

[0169] TAIC: triallyl isocyanurate, purchased from Chin Yu Enterprise Co., Ltd.

[0170] BMI-70: 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, purchased from KI Chemicals.

[0171] SC-2500SVJ: spherical silica, purchased from Admatechs.

[0172] 25B: 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, purchased from NOF Corporation.

[0173] Toluene: purchased from Sinopec. The toluene content is expressed as "appropriate amount", which means that the toluene content is adjusted to a solid content of 60% to 68% (S / C = 60% to 68%) of the resin composition.

[0174] Synthesis Example 1: Preparation of St-VBCB-St Block Copolymer

[0175] At 40°C, 1 liter of tetrahydrofuran (THF) from which water has been removed is added to a Schlenk reaction bottle, and vacuum is drawn under a liquid nitrogen environment, and nitrogen is passed through. The above steps are repeated three times, and 0.0164 g of n-butyl lithium is added, and the mixture is rapidly stirred. Styrene (hereinafter referred to as St) is first added, and 4-vinylbenzocyclobutene (hereinafter referred to as VBCB) is added after reacting for 10 hours, and St is added after continuing to react for 10 hours (the mass ratio of the three is 22.5:55:22.5, a total of 50 ml), and the reaction is continued for 10 hours to obtain a compound represented by formula (4) with a VBCB content of 55 wt%, wherein x+z=2-5, y=12-15, and is marked as A1.

[0176] At 30°C, add 1 liter of cyclohexane from which water has been removed to a Schlenk reaction bottle, evacuate under liquid nitrogen environment, pass nitrogen, repeat the above steps three times, add 0.0087 g of n-butyl lithium, and stir rapidly. Add St first, react for 18 hours, add VBCB, continue to react for 18 hours, add St (the mass ratio of the three is 12.5:75:12.5, a total of 50 ml), continue to react for 18 hours to obtain a compound represented by formula (4) with a VBCB content of 75 wt%, wherein x+z=5-10, y=15-20, and is marked as A2.

[0177] Under ice water at 0°C, add 1 liter of THF from which water has been removed to a Schlenk reaction flask, evacuate under liquid nitrogen, pass nitrogen, repeat the above steps three times, add 0.0042 g of tert-butyl lithium, and stir rapidly. Add St first, react for 6 hours, add VBCB, continue to react for 6 hours, add St (the mass ratio of the three is 5:90:5, a total of 50 ml), continue to react for 6 hours to obtain a compound represented by formula (4) with a VBCB content of 90 wt%, wherein x+z=5-8, y=38-42, and is marked as A3.

[0178] Synthesis Example 2: Preparation of Ethylvinylbenzene-VBCB-Ethylvinylbenzene Block Copolymer

[0179] At 25°C, 1 liter of THF from which water has been removed is added to a Schlenk reaction bottle, and vacuum is drawn under a liquid nitrogen environment, and nitrogen is passed through, and the above steps are repeated three times, and 0.0027 g of n-butyl lithium is added, and the mixture is stirred rapidly. First, m-ethylvinylbenzene is added, and VBCB is added after reacting for 12 hours, and m-ethylvinylbenzene is added after continuing the reaction for 12 hours (the mass ratio of the three is 12.5:75:12.5, a total of 50 ml), and the reaction is continued for 12 hours to obtain a compound represented by formula (6) with a VBCB content of 75 wt%, wherein x+z=15-19, y=50-54, and is marked as A4.

[0180] Synthesis Example 3: Preparation of DVB-VBCB-DVB Block Copolymer

[0181] At 25°C, 1 liter of THF from which water has been removed is added to a Schlenk reaction bottle, and vacuum is drawn under a liquid nitrogen environment, and nitrogen is passed through, and the above steps are repeated three times, and 0.00054 g of n-butyl lithium is added, and the mixture is rapidly stirred. First, o-divinylbenzene (o-DVB) is added, and VBCB is added after reacting for 4 hours, and o-DVB is added after continuing to react for 4 hours (the mass ratio of the three is 12.5:75:12.5, a total of 10 ml), and the reaction is continued for 4 hours to obtain a compound represented by formula (10) with a VBCB content of 75 wt%, wherein x+z=20-25, y=65-70, and is marked as A5.

[0182] Synthesis Example 4: Preparation of BVPE-VBCB-BVPE block copolymer

[0183] At 25°C, 1 liter of THF from which water has been removed is added to a Schlenk reaction bottle, and vacuum is drawn under a liquid nitrogen environment, and nitrogen is passed through, and the above steps are repeated three times, and 0.00026 g of n-butyl lithium is added, and the mixture is rapidly stirred. First, p-bis(vinylphenyl)ethane (BVPE) is added, and VBCB is added after the reaction for 4 hours, and BVPE is added after the reaction for another 4 hours (the mass ratio of the three is 5:90:5, a total of 10 ml), and the reaction is continued for another 4 hours to obtain a compound represented by formula (11) with a VBCB content of 90 wt%, wherein x+z=40-44, y=65-70, and is marked as A6.

[0184] Synthesis Example 5: Preparation of St-VBCB random copolymer

[0185] Add 21 g of n-propyl acetate and 50 g of a mixture of VBCB and St (wherein VBCB accounts for 90% by mass) into the reaction bottle, stir evenly, continue to add 0.28 g of boron trifluoride diethyl ether, heat to 40 ° C and react for 72 hours to obtain a compound represented by formula (12) with a VBCB content of 90 wt%, wherein m = 2 to 44, n = 12 to 70, marked as A7.

[0186] Add 50 g of n-butyl acetate and 50 g of a mixture of VBCB and St (wherein VBCB accounts for 55% by mass) into the reaction bottle, stir evenly, continue to add 0.98 g of boron trifluoride methyl ether, and react at 20°C for 36 hours to obtain a compound represented by formula (12) with a VBCB content of 55 wt%, wherein m=2-44, n=12-70, and is marked as A8.

[0187] Synthesis Example 6: Preparation of Ethylvinylbenzene-VBCB Random Copolymer

[0188] 70 g of tetrahydrofuran and a mixture of 50 g of VBCB and p-ethylvinylbenzene (wherein VBCB accounts for 75% by mass) were added to the reaction bottle, stirred evenly, and 0.92 g of aluminum chloride was added, and the temperature was raised to 70° C. for reaction for 4 hours to obtain a compound represented by formula (13) with a VBCB content of 75 wt%, wherein m=2-44, n=12-70, and marked as A9.

[0189] Synthesis Example 7: Preparation of DVB-VBCB random copolymer

[0190] Add 23 g of n-propyl acetate and a mixture of 10 g of VBCB and m-divinylbenzene (m-DVB) (wherein VBCB accounts for 75% by mass) into the reaction bottle, stir evenly, continue to add 0.22 g of boron trifluoride diethyl ether, heat to 40 ° C and react for 4 hours to obtain a compound represented by formula (17) with a VBCB content of 75 wt%, wherein m = 2 to 44, n = 12 to 70, marked as A10.

[0191] Synthesis Example 8: Preparation of BVPE-VBCB random copolymer

[0192] Add 20 g of n-propyl acetate and 10 g of a mixture of VBCB and BVPE (wherein VBCB accounts for 90% by mass) into the reaction bottle, stir evenly, continue to add 0.21 g of boron trifluoride diethyl ether, heat to 40 ° C and react for 4 hours to obtain a compound represented by formula (19) with a VBCB content of 90 wt%, wherein m = 2 to 44, n = 12 to 70, and is marked as A11.

[0193] Synthesis Example 9: Preparation of St-VBCB random copolymer (VBCB content 50 wt%)

[0194] Add 50 g of n-propyl acetate and 50 g of a mixture of VBCB and St (of which VBCB accounts for 50% by mass) into the reaction bottle, stir evenly, continue to add 1.09 g of boron trifluoride diethyl ether, heat to 40°C and react for 72 hours to obtain a St-VBCB random copolymer (VBCB content is 50wt%), marked as B1.

[0195] Synthesis Example 10: Preparation of St-VBCB random copolymer (VBCB content 30 wt%)

[0196] Add 50 g of n-propyl acetate and 50 g of a mixture of VBCB and St (of which VBCB accounts for 30% by mass) into the reaction bottle, stir evenly, continue to add 1.09 g of boron trifluoride diethyl ether, heat to 40°C and react for 72 hours to obtain a St-VBCB random copolymer (VBCB content is 30wt%), marked as B2.

[0197] Synthesis Example 11: Preparation of VBCB homopolymer (VBCB content: 100 wt%)

[0198] Add 50 g of n-propyl acetate and 50 g of VBCB into the reaction bottle, stir evenly, continue to add 1.09 g of boron trifluoride diethyl ether, raise the temperature to 40° C. and react for 48 hours to obtain VBCB homopolymer (VBCB content is 100 wt%), marked as B3.

[0199] Synthesis Example 12: Preparation of BCB-modified DVB-St copolymer (structural formula as follows)

[0200]

[0201] First, the reactor was evacuated and nitrogen was passed through for three times, and then 2.5 moles of 4-bromobenzocyclobutene, 7.5 moles of divinylbenzene, 0.0075 moles of palladium acetate, 0.03 moles of tri(o-methylphenyl)phosphine, 2.63 moles of triethylamine and 2 liters of dry acetonitrile were added. After the system was replaced with nitrogen once more, the water bath was heated to 58°C. After 48 hours, the reaction was terminated, and a large amount of salt was precipitated after cooling to room temperature, and then filtered to remove solids and palladium black. The filtrate was concentrated by rotary evaporation to remove the solvent and then filtered with silica gel. The filtrate obtained by this filtration was distilled under reduced pressure at 80°C to 90°C to remove the unreacted raw materials to obtain a brown-yellow liquid, which was then purified by distillation under reduced pressure at 90°C and 150°C to obtain a benzocyclobutene monosubstituted divinylbenzene monomer.

[0202] Add 0.025 mol of the benzocyclobutene monosubstituted divinylbenzene monomer and 0.025 mol of styrene monomer into a single-necked bottle. Cover with a rubber stopper, evacuate and pass nitrogen for 3 times, then inject 22 ml of toluene. Stir the reaction at 100°C for 10 hours, cool to room temperature, and precipitate with methanol 3 times to obtain a white powder, which is a BCB-modified DVB-St copolymer, labeled as B4.

[0203] Synthesis Example 13: Preparation of the compound represented by formula (3-1)

[0204] Add 31.2 g of NaH and 400 ml of anhydrous tetrahydrofuran to a 1-liter three-necked flask, introduce nitrogen, stir and heat to 50°C, dissolve 75.2 g of p-hydroxybenzaldehyde in 200 ml of anhydrous tetrahydrofuran, slowly add dropwise to the three-necked flask, continue to react for 4 hours after the addition is complete, then dissolve 34.7 g of hexachlorocyclotriphosphazene in 200 ml of anhydrous tetrahydrofuran, add to the three-necked flask, heat to 65°C, react for 48 hours, filter, and rotary evaporate to obtain an intermediate product.

[0205] At room temperature, add 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml into a three-necked flask, stir, slowly add 100 g of potassium tert-butoxide, react for 2 hours, add 600 g of calcium bromide, stir and react for 24 hours, add acetic acid aqueous solution, adjust the pH value to 7 to 8, remove tetrahydrofuran in the system by rotary evaporation, add ethyl acetate, separate the liquids, collect the oil phase, remove ethyl acetate by rotary evaporation, use a mixed solution of cyclohexane and ethyl acetate as the mobile phase (cyclohexane: ethyl acetate = 500: 1 to 10: 1), separate and purify by silica gel chromatography, and the obtained product is the compound shown in formula (3-1) with a pH value of 8.

[0206] Synthesis Example 14: Preparation of the compound represented by formula (3-2)

[0207] At room temperature, 100 g of hexachlorocyclotriphosphazene, 198 g of triethylamine and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 110 g of o-hydroxybenzaldehyde was slowly dropped into the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 50°C and the reaction was continued for 64 hours. Then, 220 ml of a tetrahydrofuran solution of p-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask. The reaction was continued for 60 hours. The mixture was filtered and rotary evaporated to obtain an intermediate product.

[0208] At room temperature, add 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml into a three-necked flask, stir, slowly add 100 g of potassium tert-butoxide, react for 2 hours, add 600 g of calcium bromide, stir and react for 24 hours, add acetic acid aqueous solution, adjust the pH value to 7 to 8, remove tetrahydrofuran in the system by rotary evaporation, add ethyl acetate, separate the liquids, collect the oil phase, remove ethyl acetate by rotary evaporation, use a mixed solution of cyclohexane and ethyl acetate as the mobile phase (cyclohexane: ethyl acetate = 500: 1 to 10: 1), separate and purify by silica gel chromatography, and the obtained product is the compound shown in formula (3-2) with a pH value of 8.

[0209] Synthesis Example 15: Preparation of the compound represented by formula (3-4)

[0210] Add 31.2 g of NaH and 400 ml of anhydrous tetrahydrofuran to a 1-liter three-necked flask, introduce nitrogen, stir and heat to 50°C, dissolve 75.2 g of o-hydroxybenzaldehyde in 200 ml of anhydrous tetrahydrofuran, slowly dropwise add to the three-necked flask, continue to react for 4 hours after the addition is complete, then dissolve 34.7 g of hexachlorocyclotriphosphazene in 200 ml of anhydrous tetrahydrofuran, add to the three-necked flask, heat to 65°C, react for 48 hours, filter, and rotary evaporate to obtain an intermediate product.

[0211] At room temperature, add 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml into a three-necked flask, stir, slowly add 100 g of potassium tert-butoxide, react for 3 hours, add 600 g of calcium bromide, stir and react for 30 hours, add acetic acid aqueous solution, adjust the pH value to 7 to 8, remove tetrahydrofuran in the system by rotary evaporation, add ethyl acetate, separate the liquids, collect the oil phase, remove ethyl acetate by rotary evaporation, use a mixed solution of cyclohexane and ethyl acetate as the mobile phase (cyclohexane: ethyl acetate = 500: 1 to 10: 1), separate and purify by silica gel chromatography, and the obtained product is the compound shown in formula (3-4) with a pH value of 8.

[0212] Synthesis Example 16: Preparation of the compound represented by formula (3-9)

[0213] At room temperature, 100 g of hexachlorocyclotriphosphazene, 198 g of triethylamine and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 110 g of o-hydroxybenzaldehyde was slowly dropped into the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 50°C and the reaction was continued for 64 hours. Then, 220 ml of a tetrahydrofuran solution of m-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask. The reaction was continued for 60 hours. The mixture was filtered and the intermediate product was obtained by rotary evaporation.

[0214] At room temperature, add 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml into a three-necked flask, stir, slowly add 100 g of potassium tert-butoxide, react for 2 hours, add 600 g of calcium bromide, stir and react for 24 hours, add acetic acid aqueous solution, adjust the pH value to 7 to 8, remove tetrahydrofuran in the system by rotary evaporation, add ethyl acetate, separate the layers, collect the oil phase, remove ethyl acetate by rotary evaporation, use a mixed solution of cyclohexane and ethyl acetate as the mobile phase (cyclohexane: ethyl acetate = 500: 1 to 10: 1), separate and purify by silica gel chromatography, and the obtained product is the compound shown in formula (3-9) with a pH value of 8.

[0215] The composition and property test results of the resin compositions of the embodiments and comparative examples of the present invention are shown in Tables 1 to 5:

[0216] [Table 1] Composition and property test results of the resin composition of the embodiment (unit: weight parts)

[0217]

[0218] [Table 2] Composition and property test results of the resin composition of the embodiment (unit: weight parts)

[0219]

[0220] [Table 3] Composition and property test results of the resin composition of the embodiment (unit: weight parts)

[0221]

[0222] [Table 4] Composition and property test results of the resin composition of the comparative example (unit: parts by weight)

[0223]

[0224] [Table 5] Composition and property test results of the resin composition of the comparative example (unit: parts by weight)

[0225]

[0226] The characteristic tests of the embodiments and comparative examples of the present invention are performed by making the test objects (also called test specimens or samples) according to the following method and then performing the tests according to specific test conditions.

[0227] (1) Precured sheet: The resin compositions of the examples or comparative examples are respectively selected and uniformly mixed to form a varnish, which is then injected into an impregnation tank. A glass fiber cloth (e.g., L-glass fiber cloth with a specification of 2116 or L-glass fiber cloth with a specification of 1080, both purchased from Asahi Co., Ltd.) is then immersed in the impregnation tank to allow the resin composition to adhere to the glass fiber cloth. The varnish is then heated at 150° C. to 170° C. to a semi-cured state (B-Stage), thereby obtaining a precured sheet.

[0228] (2) Copper foil substrate (8-ply, formed by pressing 8 prepregs): 2 ultra-low surface roughness (HVLP) copper foils with a thickness of 18 microns and 8 2116 L-glass fiber cloths were prepared to impregnate the prepregs prepared by the samples to be tested (each group of examples or comparative examples), and the resin content of each prepreg was about 53%. One HVLP copper foil, eight prepregs, and one HVLP copper foil were stacked in order, and pressed under vacuum conditions, a pressure of 500 psi, and 200° C. for 2 hours to form a copper foil substrate, wherein the 8 stacked prepregs were cured to form an insulating layer between the two copper foils, and the resin content of the insulating layer was about 53%.

[0229] (3) Copper-free substrate (8-ply, formed by pressing together 8 prepregs): The above copper foil substrate (8-ply) is etched to remove 2 copper foils to obtain a copper-free substrate (8-ply). The copper-free substrate is formed by pressing together 8 prepregs. The resin content of the copper-free substrate is about 53%.

[0230] (4) Copper-free substrate (2-ply, formed by laminating two prepregs): Two ultra-low surface roughness (HVLP) copper foils with a thickness of 18 microns and two 1080 L-glass fiber cloths were prepared to impregnate the prepregs made from each sample to be tested (each group of examples or comparative examples), and the copper foil, two prepregs and copper foil were stacked in the order of the copper foil, the two prepregs and the copper foil, and pressed for 2 hours under vacuum conditions, a pressure of 500 psi and 200° C. to form a copper-containing substrate (2-ply, formed by laminating two prepregs). Then, the copper foil-containing substrate (2-ply) was etched to remove the copper foils on both sides to obtain a copper-free substrate (2-ply), which was formed by laminating two prepregs, and the resin content of the copper-free substrate (2-ply) was about 70%.

[0231] (5) Ten-layer board: Prepare EM-LX copper-containing substrate (available from Taiwan Optoelectronics Materials Co., Ltd., with a thickness of 3 mils, using 1078E-glass fiber cloth and 18-micron thick HTE copper foil), and make circuits on the surface copper foil of the copper-containing substrate (such as known exposure, lithography, and etching processes, which are not repeated here) to make a core board. After the core board is made, prepare a second prepreg (made from the resin composition of each group of embodiments and comparative examples, using 1027L-glass fiber cloth), overlap a second prepreg on both sides of the core board, and overlap another 18-micron thick HTE copper foil on the other side of the second prepreg relative to the core board, and press and cure for 2 hours under vacuum conditions, high temperature (200°C) and high pressure (360psi) to complete the first pressing. Then perform a drilling process to make alignment holes, and then perform an in-hole metallization process and a circuit process to complete the first layer-increasing step, thereby forming a four-layer board. Repeat the above-mentioned layer-building steps to form a six-layer board (second layer-building, second pressing), an eight-layer board (third layer-building, third pressing), and finally a ten-layer board (fourth layer-building, fourth pressing).

[0232] The test methods and characteristic analysis items of the samples to be tested are as follows:

[0233] 1. Reflow soldering warpage

[0234] The above ten-layer board was selected, and samples with length and width of 150mm×78mm were cut. The ten-layer board was subjected to reflow soldering using the TherMoire instrument sold by Akrometrix and referring to the published Full-field Signed Warpage test method. During the process, the temperature was first raised from 30°C to 260°C, and then the maximum and minimum warpage values ​​of the ten-layer board at 260°C and 30°C were measured. The difference between the two values ​​is the reflow soldering warpage (= maximum warpage - minimum warpage), in μm. When the difference in reflow soldering warpage is greater than or equal to 1 μm, it means that there is a significant difference between different samples (there is a significant technical difficulty).

[0235] 2. Percent of thermal expansion, z-axis, Z-PTE

[0236] The aforementioned copper-free substrate (8-ply) was used to prepare the test samples, and the thermal mechanical analysis (TMA) was performed according to the method of IPC-TM-650 2.4.24.5. The temperature was raised from 50°C to 260°C at a heating rate of 10°C / min, and the Z-axis thermal expansion coefficient (in %) of each test sample within the temperature range of 50°C to 260°C was measured. When the Z-axis thermal expansion coefficient is less than or equal to 1%, the difference in the Z-axis thermal expansion coefficient is greater than or equal to 2%, which means that there are significant differences between different samples (there is a significant technical difficulty).

[0237] 3. Heat resistance of multilayer boards

[0238] Prepare a 2116 L-glass fiber cloth impregnated with each sample to be tested (each group of examples or comparative examples) to obtain a prepreg (the resin content of each prepreg is about 53%), and laminate a piece of ultra-low surface roughness copper foil (thickness of 18 microns) on both sides of the prepreg, and then press and cure for 2 hours under vacuum, high temperature (200°C) and high pressure (500psi) conditions to obtain a copper-containing core board. Then, the copper foil on both sides of the copper-containing core board is etched to remove the copper foil to obtain a copper-free core board (thickness of 5 mils). Prepare 3 copper-free core boards according to this method. Next, two ultra-low surface roughness copper foils (thickness of 18 microns) and eight 1080 L-glass fiber cloths were prepared to impregnate the prepregs (the resin content of each prepreg was about 70%) prepared by impregnating the samples to be tested (each set of embodiments or comparative examples). According to the copper foil, two prepregs (made with 1080 L-glass fiber cloth), one copper-free core board, two prepregs (made with 1080 L-glass fiber cloth), one copper-free core board, two prepregs (made with 1080 L-glass fiber cloth), one copper-free core board, two prepregs (made with 1080 L-glass fiber cloth), one copper-free core board, two prepregs (made with 1080 L-glass fiber cloth), -glass fiber cloth), copper foil, and laminated in order, and pressed for 2 hours under vacuum conditions, pressure of 500psi, and 200℃ to form an eight-layer board with copper foil on the outer layer, which was then cut into rectangular samples (18 inches long and 16 inches wide). On the surface of the rectangular sample, 20 holes × 25 holes (500 holes) were made using circuit board drilling technology, with a hole diameter of 0.3mm. The vertical distance between adjacent hole walls has six designs of 0.25 / 0.3 / 0.35 / 0.4 / 0.5 / 0.7mm, and each of the six designs is a group. The entire board surface has a total of 24 groups and 72,000 holes. Electroplated copper is then formed on the hole wall, and two adjacent groups are randomly selected from the edge of the board or the board as a test sample, and a total of three test samples are taken.

[0239] The above-mentioned multilayer board heat resistance test sample is placed horizontally on (i.e. in contact with) the tin liquid surface in the tin furnace at a constant temperature of 288°C. During each test, one side of the sample is placed on the tin surface for 10 seconds, then taken out and cooled at room temperature for 30 seconds. This is recorded as one time and the subsequent test does not need to be turned over. Repeat 10 times. Then the sample after 10 times of tinning is sliced ​​and prepared in the drilling area, and an optical microscope is used to observe whether the inner layer of the sample has exploded. Three samples are tested in each group. If there is no bursting in the test result, it is marked as "O", and if there is a bursting in the test result, it is marked as "X". For example, if all three samples have no bursting, it is marked as "OOO", if two of the three samples have no bursting and one bursting, it is marked as "OOX", if one of the three samples has no bursting and two bursting, it is marked as "OXX", and if all three samples have bursting, it is marked as "XXX". The above-mentioned "board bursting" can be understood as interlayer peeling or blistering phenomenon. Board bursting can occur between any layers of the substrate. For example, interlayer peeling between insulating layers can be called board bursting. For example, blistering and separation between copper foil and insulating layer can also be called board bursting.

[0240] 4. Dielectric loss aging rate (Df aging rate)

[0241] The aforementioned copper-free substrate (2-ply) was cut into square samples of 8 cm × 8 cm. The dielectric loss value of each sample was measured at room temperature (about 25°C) and at a frequency of 10 GHz using a microwave dielectrometer (purchased from AET, Japan) with reference to the method described in JIS C2565, and marked as Df1. After the test, the sample was placed in an oven at 125°C for 240 hours, and the dielectric loss value was tested again, marked as Df2. Calculated using the following formula: Df aging rate = ((Df2-Df1) / Df1) × 100%.

[0242] 5. Temperature coefficient of dielectric constant (TcDk)

[0243] The aforementioned copper-free substrate (2-ply) was cut into square samples of 8 cm×8 cm, and the SPDR resonant cavity analyzer (split post dielectric resonant cavity, purchased from Waveray) was used to measure the change of the dielectric constant Dk of the sample at a frequency of 10 GHz and a relative humidity of 65%, and the temperature range of the sample was between 25°C and 150°C according to the method described in IPC-TM-6502.5.5.13. The smaller the value of the dielectric constant temperature coefficient TcDk, the smaller the change value of the dielectric constant Dk when the temperature rises, which means that the dielectric constant of the insulation layer of the copper-free substrate is more stable, and the signal transmission of the subsequently manufactured printed circuit board in a high temperature environment is also more stable.

[0244] 6. Temperature coefficient of dielectric loss factor (TcDf)

[0245] The aforementioned copper-free substrate (2-ply) was cut into square samples of 8 cm×8 cm, and the sample was measured using a SPDR resonant cavity analyzer (split post dielectric resonant cavity, purchased from Waveray) with reference to the method described in IPC-TM-6502.5.5.13 at a frequency of 10 GHz and a relative humidity of 65%, with the change in the dielectric loss Df of the sample between 25°C and 150°C. The smaller the value of the dielectric loss temperature coefficient TcDf, the smaller the change in the dielectric loss Df when the temperature rises, which means that the dielectric loss of the insulating layer of the copper-free substrate is more stable, and the signal integrity of the subsequently manufactured printed circuit board in a high temperature environment is better.

[0246] By referring to the characteristic test results in Table 1 to Table 5, the following phenomena can be clearly observed:

[0247] 1. Embodiments E1 to E15 use copolymers having structural units formed by monomers represented by formula (1) and structural units formed by monomers represented by formula (2), wherein the monomer represented by formula (1) may be, for example, styrene (St), ethylvinylbenzene, divinylbenzene (DVB) or bis(vinylphenyl)ethane (BVPE), wherein the monomer represented by formula (2) may be, for example, 4-vinylbenzocyclobutene (VBCB), and the content of the structural units formed by the monomers represented by formula (2) in the copolymer is 55 wt % to 90 wt % (the copolymer is hereinafter referred to as the copolymer of the present invention). The copolymers in Embodiments E1 to E8 and E14 to E15 are block copolymers, and the copolymers in Embodiments E9 to E13 are random copolymers. In Comparative Examples C1 to C2, the amount of the compound represented by formula (3) is outside the scope of the present invention; in the polymers in Comparative Examples C3 to C5, the content of the structural unit formed by the monomer represented by formula (2) in the copolymer is outside the scope of the present invention; in Comparative Example C6, a BCB-modified DVB-St copolymer different from the copolymer of the present invention is used; and in Comparative Examples C7 to C10, a polyolefin different from the copolymer of the present invention is used.

[0248] 2. It can be determined from Examples E1 to E15 that the resin composition of the present invention and its products can be improved in one, more or all of the following properties: reflow soldering warpage, Z-axis thermal expansion coefficient, dielectric loss aging rate, dielectric constant temperature coefficient, dielectric loss temperature coefficient, heat resistance of multilayer boards, etc.

[0249] 3. By comparing Examples E1 to E15 and Comparative Examples C1 to C2, it can be found that compared with 100 parts by weight of the copolymer of the present invention, if the content of the compound represented by formula (3) is not in the range of 10 parts by weight to 60 parts by weight, the reflow soldering warpage, Z-axis thermal expansion coefficient, heat resistance of the multilayer board and dielectric loss temperature coefficient are significantly poorer.

[0250] 4. By comparing Examples E1 to E15 and Comparative Examples C3 to C6, it can be found that compared with the copolymer of the present invention, if a copolymer in which the content of the structural unit formed by the monomer represented by formula (2) is 50 wt% (Comparative Example C3), or a copolymer in which the content of the structural unit formed by the monomer represented by formula (2) is 30 wt% (Comparative Example C4), or a homopolymer in which the content of the structural unit formed by the monomer represented by formula (2) is 100 wt% (Comparative Example C5), or a BCB-modified DVB-St copolymer (Comparative Example C6), the reflow soldering warpage, heat resistance of the multilayer board, dielectric constant temperature coefficient and dielectric loss temperature coefficient are significantly inferior.

[0251] 5. By comparing Examples E1 to E15 and Comparative Examples C7 to C10, it can be found that compared with the copolymer of the present invention, if a polyolefin different from the copolymer of the present invention is used, the reflow soldering warpage, Z-axis thermal expansion coefficient, multilayer board heat resistance, dielectric loss aging rate, dielectric constant temperature coefficient and dielectric loss temperature coefficient are significantly worse.

[0252] 6. By comparing Examples E1 to E8, E14 to E15 and Examples E9 to E13, it can be found that for the copolymer of the present invention, compared with the random copolymer, if the block copolymer is used, the dielectric constant temperature coefficient and the dielectric loss temperature coefficient can be more significantly improved.

[0253] The above implementation modes and examples are essentially only for auxiliary explanation and are not intended to limit the embodiments of the present invention or the application or use of these embodiments. In the present invention, a term similar to "example" means "as an example, example or illustration". Any exemplary implementation form herein is not necessarily interpreted as being preferred or more advantageous than other implementation forms, unless otherwise specified.

[0254] In addition, although at least one exemplary embodiment or comparative example has been proposed in the aforementioned embodiment, it should be understood that the present invention can still have a large number of variations. It should also be understood that the embodiments herein are not intended to limit the scope, use or configuration of the requested technical solution in any way. On the contrary, the aforementioned embodiment can provide a simple guide for those skilled in the art to implement one or more of the aforementioned embodiments and their equivalents. In addition, the claims include known equivalents and all foreseeable equivalents when the present patent application is filed.

Claims

1. A resin composition, characterized in that The resin composition comprises the following components: (A) 100 parts by weight of a copolymer, the copolymer having a structural unit formed from a monomer represented by formula (1) and a structural unit formed from a monomer represented by formula (2), wherein the content of the structural unit formed from the monomer represented by formula (2) accounts for 55 wt % to 90 wt % of the copolymer; and (B) 10 to 60 parts by weight of a compound represented by formula (3), In the formula (1), R1 to R5 are each independently selected from a hydrogen atom, a C1 to C3 alkyl group, a C2 to C3 alkenyl group, a phenyl group, a C1 to C3 alkyl-substituted phenyl group, a C2 to C3 alkenyl-substituted phenyl group, and a C2 to C3 alkenylphenyl C1 to C3 alkylene group; In the formula (2), R6 to R9 are each independently selected from a hydrogen atom, a C1 to C3 alkyl group and a C2 to C3 alkenyl group, and at least one of R6 to R9 is a C2 to C3 alkenyl group; In the formula (3), n is an integer of 3 to 6, and X and Y each independently represent an o-vinylphenoxy group, a m-vinylphenoxy group or a p-vinylphenoxy group.

2. The resin composition according to claim 1, characterized in that The monomer represented by formula (1) includes any one of the monomer represented by formula (1-1), the monomer represented by formula (1-2), the monomer represented by formula (1-3), and the monomer represented by formula (1-4) or a combination thereof, and the monomer represented by formula (2) includes the monomer represented by formula (2-1), 3. The resin composition according to claim 1, characterized in that The copolymer includes any one of a block copolymer and a random copolymer or a combination thereof.

4. The resin composition according to claim 1, characterized in that The copolymer includes any one or a combination of the copolymers represented by the following formulas (4) to (19): In the above formulas (4) to (19), m, n, x, y, and z are each independently a positive integer and satisfy the following relationship: 2≦m≦44, 12≦n≦70, 2≦x+z≦44, 12≦y≦70.

5. The resin composition according to claim 1, characterized in that The compound represented by formula (3) includes any one or a combination of the compound represented by formula (3-1) to the compound represented by formula (3-14), 6. The resin composition according to claim 1, characterized in that The resin composition further comprises 1 to 30 parts by weight of a cross-linking agent containing unsaturated carbon-carbon double bonds, wherein the cross-linking agent containing unsaturated carbon-carbon double bonds is any one of bis(vinylphenyl)ethane, divinylbenzene, divinylnaphthalene, divinylbiphenyl, triallyl isocyanurate, triallyl cyanurate, vinylbenzocyclobutene, di(vinylbenzyl)ether, trivinylcyclohexane, diallyl bisphenol A, difunctional or higher acrylate, butadiene, decadiene, octadiene, or a combination thereof.

7. The resin composition according to claim 1, characterized in that The resin composition further comprises any one of a polyolefin different from the copolymer, a polyphenylene ether resin containing unsaturated carbon-carbon double bonds, a benzoxazine resin, an epoxy resin, a polyester resin, a phenol resin, an amine curing agent, a polyamide, a polyimide, styrene maleic anhydride, a maleimide resin, a cyanate ester, and a maleimide triazine resin, or a combination thereof.

8. The resin composition according to claim 1, characterized in that The resin composition further comprises any one of an inorganic filler, a flame retardant different from the compound represented by the formula (3), a hardening accelerator, an inhibitor, a solvent, a silane coupling agent, a dye, and a toughening agent, or a combination thereof.

9. A product, characterized in that The product is made of the resin composition according to any one of claims 1 to 8, and includes a prepreg, a resin film, a laminate or a printed circuit board.

10. The article according to claim 9, characterized in that The product has one or more of the following characteristics: The reflow soldering warpage measured by the Full-field Signed Warpage test method is less than or equal to 10μm; The Z-axis thermal expansion rate measured according to IPC-TM-650 2.4.24.5 is less than or equal to 1.0%; After standing at a constant temperature of 125°C for 240 hours, the dielectric loss aging rate calculated by the dielectric loss measured at a frequency of 10 GHz according to the method of JIS C2565 is less than or equal to 60%; The dielectric constant temperature coefficient measured according to IPC-TM-650 2.5.5.13 is less than or equal to 70ppm / ℃; The dielectric loss temperature coefficient measured according to IPC-TM-650 2.5.5.13 is less than or equal to 4000ppm / ℃.

Citation Information

Patent Citations

  • Imide-linked maleimide and polymaleimide compounds

    TW200508284A

  • Curable resin composition

    US20070129502A1

  • Polyphenylene oxide resin, method of preparing polyphenylene oxide resin, polyphenylene oxide prepolymer and resin composition

    US20160185904A1

Cited By

  • A phosphazene derivative-containing cathode slurry composition, cathode and electrochemical device comprising the same

    TWI913150B